Bronchial thermoplasty in asthma: current perspectives - Laxmanan, Balaji (J Asthma Allergy, 2015)
Bronchial thermoplasty (BT) is a novel therapy for patients with severe asthma. Using radio frequency thermal energy, it aims to reduce the airway smooth muscle mass. Several clinical trials have demonstrated improvements in asthma-related quality of life and a reduction in the number of exacerbations following treatment with BT. In addition, recent data has demonstrated the long-term safety of the procedure as well as sustained improvements in rates of asthma exacerbations, reduction in health care utilization, and improved quality of life. Further study is needed to elucidate the underlying mechanisms that result in these improvements. In addition, improved characterization of the asthma subphenotypes likely to exhibit the largest clinical benefit is a critical step in determining the precise role of BT in the management of severe asthma.